Derangement of the T‐cell repertoire in patients with B‐cell non‐Hodgkin's lymphoma. (22nd August 2014) - Fozza, Claudio; Corda, Giovanna; Virdis, Patrizia; Contini, Salvatore; Barraqueddu, Francesca; Galleu, Antonio; Isoni, Antonella; Cossu, Antonella; Dore, Fausto; Careddu, Maria G.; Bonfigli, Silvana; Giannico, Barbara; et al.
Abstract: Although a number of studies suggest that different immune pathways may play a role in the pathogenesis of non‐Hodgkin's lymphomas (NHL), the shape of the T‐cell compartment has been only superficially explored in these patients. In our study, we analyzed the peripheral T‐cell receptor (TCR) repertoire and the distribution of different T‐cell subsets – including regulatory T cells (Treg) – in 30 patients with NHL, by combining flow cytometry and spectratyping. We first demonstrated by flow cytometry an increased frequency of expanded T‐cell subpopulations expressing the same TCR beta variable (BV) subfamilies in CD8+ cells from NHL patients when compared with healthy controls, beside a higher frequency of Treg. Moreover, NHL patients were characterized by a higher percentage of BVs showing a skewed CDR3 profile both in CD4+ and CD8+ cells when analyzed by spectratyping. Our data suggest that the T‐cell branch of the immune system of patients with B‐cell NHL is deeply deranged, as witnessed by the increased degree of activation and skewing of their TCR repertoire along with the higher frequency of Treg.